HUBUNGAN PENGETAHUAN DAN MOTIVASI IBU TENTANG PEMBERIAN AIR SUSU IBU (ASI) EKSLUSIF DI KELURAHAN PALMERAH WILAYAH KERJA PUSKESMAS PAAL MERAH II KOTA JAMBI - Hesty Hesty (Jurnal Akademika Baiturrahim Jambi, 2018)
Breast milk is the most perfect milk for children up to the age of two, and it is even advisable to give exclusive breastfeeding for the first six months, and it is recommended for breastfeeding colostrum when first breastmilking comes out. Breast milk is contained many antibodies that are good for the baby's immune. This research is a quantitative research by using prospective approach that is design by looking forward from an event that related to the occurrence of the research or incident that happened at the same time. The result showed that respondents with good knowledge in breastfeeding were 25 (71,4%) of respondents. From Chi Square analysis results obtained p-value = 0.044 <0.05, it can be concluded that there is a significant relationship between knowledge of mother with breastfeeding in Kelurahan Palmerah working area Puskesmas Paalmerah II Kota Jambi. From Chi Square analysis results obtained p-value = 0.046 <0.05, it can be concluded that there is a significant relationship between motivation with breastfeeding in Kelurahan Palmerah working area Puskesmas Paalmerah II Kota Jambi.